Inverse analysis of the heat conduction process induced by impinging jet (Archives of Mechanics - Test, 2002)
This paper presents an analysis of the cooling process of a solid, induced by the impingement of an air jet. Solutions of the inverse heat conduction problem were obtained by applying the heat functions to formulate the base functions of the Finite Element Method. The applied heat functions identically satisfy the heat conduction equation in dimensionless co-ordinates. The minimisation of the functional, presented in this paper, leads to the solutions of the analysed problem. The temperature distribution of the analysed solid was determined by solving the inverse heat conduction problem by means of the temperature measurements taken inside the solid. Properties of the heat function were applied to reconstruct the distribution of the Bi number on the heat exchange surface; this in turn enables to determine the heat transfer coefficient on the analysed surface. The results of the analysis were compared with the data found in the literature.